2015
DOI: 10.1128/aem.01145-15
|View full text |Cite
|
Sign up to set email alerts
|

Three of a Kind: Genetically Similar Tsukamurella Phages TIN2, TIN3, and TIN4

Abstract: bThree Tsukamurella phages, TIN2, TIN3, and TIN4, were isolated from activated sludge treatment plants located in Victoria, Australia, using conventional enrichment techniques. Illumina and 454 whole-genome sequencing of these Siphoviridae viruses revealed that they had similar genome sequences, ranging in size between 76,268 bp and 76,964 bp. All three phages shared 74% nucleotide sequence identity to the previously described Gordonia phage GTE7. Genome sequencing suggested that phage TIN3 had suffered a muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Despite an understanding of the activated sludge process and the viruses involved, little research into phage communities had been conducted prior to 2011 [94]. With the advent of next-generation DNA sequencing (NGS) of isolated phages and metagenomics studies, this situation has improved [95,96,97,98,99,100,101,102,103,104,105,106]. It is now clear that the genomes of many bacteria present in activated sludge systems contain CRISPR-Cas regions, suggesting that these have in the past been infected by phage, and therefore their presence makes the problem of determining host/phage relationships in the absence of conventional ability to culture host cells, and consequently phage recovery [107].…”
Section: Bacteriophages In Artificial Environmentsmentioning
confidence: 99%
“…Despite an understanding of the activated sludge process and the viruses involved, little research into phage communities had been conducted prior to 2011 [94]. With the advent of next-generation DNA sequencing (NGS) of isolated phages and metagenomics studies, this situation has improved [95,96,97,98,99,100,101,102,103,104,105,106]. It is now clear that the genomes of many bacteria present in activated sludge systems contain CRISPR-Cas regions, suggesting that these have in the past been infected by phage, and therefore their presence makes the problem of determining host/phage relationships in the absence of conventional ability to culture host cells, and consequently phage recovery [107].…”
Section: Bacteriophages In Artificial Environmentsmentioning
confidence: 99%
“…This study indicated that all strains of pond species were considered multidrug resistant and could lead to the emergence of ESBL bacteria, posing a threat to human health upon exposure. Furthermore, nanopore sequencing technology has also been applied to industrial wastewater, [ 93 ] activated sludge, [ 94 ] animal husbandry, [ 95 ] medical waste, [ 96 ] and other environments.…”
Section: Nanopore Sequencing Technology For Microorganisms Detectionmentioning
confidence: 99%
“…It is clear that phages have evolved to overcome these powerful mechanisms as they can be isolated readily from activated sludge plants, and are capable of lysing many Mycolata members including the important foam stabilizing Gordonia (Petrovski et al 2011d(Petrovski et al , 2012bLiu et al 2015;Dyson et al 2015a;Pope et al 2017;Franco et al 2021), Rhodococcus (Shibayama and Dabbs 2011;Summer et al 2011;Petrovski et al 2011bPetrovski et al , 2012aPetrovski et al , 2013aPetrovski et al , 2013b, Tsukamurella (Petrovski et al 2011c;Dyson et al 2015b) and Nocardia (Pulverer et al 1975;Stratton et al 1996;Taylor et al 2019). Phages isolated and characterized to date are all double-stranded DNA phages that belong mainly to the Siphoviridae family, which all share similar shaped capsids with long non-contractile tails, although differing markedly in their size (Fig.…”
Section: How To Control Foaming?mentioning
confidence: 99%